Effects of supportive and minimalist footwear on standing balance and walking stability in older women - Ameer Nor Azhar; Shannon E. Munteanu; Hylton B. Menz (Journal of Foot and Ankle Research, 2023)
Abstract Background Footwear has been shown to influence balance and is an important consideration in relation to the prevention of falls. However, it remains unclear as to what type of footwear is most beneficial for balance in older people: sturdy, supportive footwear, or minimalist footwear to maximise plantar sensory input. The objectives of this study were therefore to compare standing balance and walking stability in older women wearing these two footwear styles, and to investigate participants' perceptions in relation to comfort, ease of use and fit. Methods Older women (n = 20) aged 66 to 82 years (mean 73.4, SD 3.9) performed a series of laboratory tests of standing balance (eyes open and closed on floor and foam rubber mat, near tandem standing) and walking stability (treadmill, level and irregular surface) using a wearable sensor motion analysis system. Participants were tested wearing supportive footwear (incorporating design features to improve balance) and minimalist footwear. Perceptions of the footwear were documented using structured questionnaires. Results There were no statistically significant differences in balance performance between the supportive and minimalist footwear. Participants perceived the supportive footwear to be significantly more attractive to self and others, easier to put on and off but heavier compared to the minimalist footwear. Overall comfort was similar between the footwear conditions, although the supportive footwear was reported to be significantly more comfortable in the heel, arch height, heel cup, heel width and forefoot width regions. Eighteen participants (90%) reported that they felt more stable in the supportive footwear and 17 (85%) reported that they would consider wearing them to reduce their risk of falling. Conclusion Balance performance and walking stability were similar in supportive footwear designed to reduce the risk of falling and minimalist footwear, although participants preferred the supportive footwear in relation to aesthetics, ease of use, comfort and perceived stability. Prospective studies are now required to ascertain the longer‐term advantages and disadvantages of these footwear styles on comfort and stability in older people. Trial registration Australian New Zealand Clinical Trials Registry. ACTRN12622001257752p, 20/9/2022 (prospectively registered).